The influence of through-thickness reinforcement geometry and pattern on delamination of fiber-reinforced composites: Part I – Experimental results. (15th January 2018) - Pappas, Georgios; Joncas, Simon; Michaud, Véronique; Botsis, John
Abstract: This experimental study reports effect of tuft geometry i.e., standard tufts and loops milled-down, and tufting pattern on Mode I interlaminar fracture in a GFRP. Standard tufting geometry is responsible for an increase in fracture resistance by 3.5–6 times than the neat composite, depending on the areal pattern. Based on 5 mm squared tufting pattern on DCB specimens with a full-length release film at laminate mid-plane and non-tufted ones, the individual contribution to fracture of tufts and ply delamination are isolated. For this pattern their superposition matches well the total fracture resistance of the normal tufted composite. Extrapolation of this simple superposition to other patterns underestimates the experimental results. Experiments also show that delamination mechanisms in tufted composites are significantly affected by tuft geometry, with a 65% increased resistance for the loop-less against the standard tufted specimens. This is attributed to the large amount of energy required for tuft pull-out compared to tuft rupture during delamination, which also triggers more extended ply delamination.